Experimental Study on the Microstructure and Expansion Characteristics of Paleosol Based on Spectral Scanning. (16th January 2021) - Ye, Wanjun; Chen, Yiqian; Gao, Chong; Xie, Tengfei; Jing, Hongjun; Deng, Yousheng
Abstract : To investigate the microstructure of paleosol and its expansion characteristics, the paleosol of the Zaosheng #3 tunnel of the Yinxi high-speed railway was studied. Based on X-ray diffraction (XRD), energy-dispersive X-ray spectroscopy (EDX), nuclear magnetic resonance (NMR), and scanning electron microscopy techniques (SEM), the microstructure of the paleosol was analyzed in terms of the mineral composition, formation elements, pore structure, and particle morphology. Five groups of undisturbed and remolded soils with different moisture contents were tested for the unloaded expansion rate and loaded expansion rate. The results show that the mineral components of the paleosol are mainly quartz, potash feldspar, calcite, and hematite, with the highest-content-component quartz accounting for 45.4% of the total content; the clay mineral composition of the paleosol has the highest content of montmorillonite at 12.3%. The elemental composition of the paleosol is dominated by Al, Si, Ca, and Fe, which form expansive mineral components such as quartz and montmorillonite, creating inherent conditions for expansibility of the paleosol. The T 2 distribution curves of the undisturbed and remolded paleosol are composed of three peaks. The pore distribution of paleosol mainly includes medium pores, followed by large pores, and the contents of small pores and superlarge pores are very small. In terms of particle contact, the undisturbed soil is mostly in the form of "surface-surface" and "surface-edge" contact, and the remolded soil is mainly in the form of "point-surface" and "point-point" contact. The unloaded expansion rate of remolded soil is approximately twice that of undisturbed soil. The rate of loaded expansion of both soils decreases with increasing moisture content.